Skunk berry or skunk currant ... - Campbell, Sandy (University of Alberta Library, 2017)
A member of the gooseberry family, skunkberries or skunk currants are found across nothern Canada. This edible berry has a strong odor and bristly. Skunkberries can be used to make jelly and were used as a traditional medicine by Indigenous people. ...